Perbandingan Penggunaan Ekstrak Daun Pepaya (Carica papaya) dan Ekstrak Daun Mint (Mentha piperita) dalam Pakan terhadap Produksi dan Kualitas Telur Burung Puyuh - Kumalasari, Rizki Wahita; Rusdi, Rusdi; Damayanti, Andi Pertiwi (Mitra Sains, 2023)
Phytobiotics are derivated from the plants which contains active compounds. They produce antibacterial and antioxidants activity and can improve the condition of the digestive tract. Papaya leaf extracts and mint leaf extracts have the potential as natural phytobiotics because they have antibacterial, antioxidant properties, can improve alimentary tract conditions and increase the absorption of nutrients in the feed. The aim of this study was to compare the utilization of papaya leaf extract (EDP) and mint leaf extract (EDM) in feed on the production and quality of quail egg. A hundried and fourty quails of 42 days age were arranged in a completely randomized design with 5 treatments and 4 replicates (7 quails per replicate). The treatment diets consisted of P0 = Basal diet only (Control), P1 = Basal diet + 100 ppm EDP, P2 = Basal diet + 200 ppm EDP, P3 = Basal diet + 100 ppm EDM and P4 = Basal diet + 200 ppm EDM. The results approved that mint leaf extract reduces in feed consumption, increase egg production and mass and reduce feed conversion values, in contrast the papaya leaf extract ​​produce non-significant on those variables. However, papaya leaf extract was able to increase more white index values and haugh unit ​​of quail egg, while mint leaf extract increased more yolk index values. The addition of 100 ppm mint leaf extract resulted in the highest value of egg production and egg mass. Therefore, the perfomance and quality of eggs in mint leaf group were better than papaya leaf group.